(untitled) (Medicine Today, 2019)
Introduction: Cesarean section is a common obstetric surgery worldwide. As incision wound in such a surgery is exposed abundantly to endometrial tissue, incision scar endometriosis can occur. This study reports a surgeon’s experience in managing such an uncommon entity. The aim of this study was to identify risk factors for developing SCE and show the clinical spectrum of presentation. This study also shows our experience in surgical management of surgical scar endometriosis. Extra pelvic endometriosis is defined as the presence and growth of functional endometrial tissue outside the pelvis. Cesarean scar endometriosis (CSE) is a rare form of extra pelvic endometriosis that is usually confused with other surgical problems leading to delay in diagnosis. Materials and Methods: We reviewed the case records of patients who were diagnosed as CSE in the surgery department of BIRDEM GENERAL HOSPITAL-2 from September 2013 till September 2018. Results: We found 8 patients of scar endometriosis in 5 years making it one of the rare conditions. The age of the patients range 23–39 years and interval from symptoms to treatment varied from 16 months to 64 months. Five patients had presented to surgery department and 3 were referred from obstetric department. Cyclic pain and swelling in scar area were the most common presenting symptoms. All patients underwent excision of the mass with no recurrence of symptoms at a follow up ranging from 9 to 60 months. Conclusion: Increasing awareness of this condition among doctors can help in early diagnosis and treatment with gratifying results. Precaution during obstetrical surgery to avoid undue contamination of the wound can reduce incidence of scar endometriosis. Medicine Today 2019 Vol.31(1): 42-45